(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Supply Chain Analysis of Medium Local Rice UD. Kerta Sari in Getasan Village, Petang District, Badung Regency, Bali Province. UD Kerta Sari is one of the institutions that carry out supply chain activities for rice commodities in Getasan Village, Petang District, Badung Regency. The goals of this research is to identify the mechanism of supply chain flow in the rice commodity which includes product flow, financial flow and information flow as well as the amount of margin, level of efficiency and farmer’s share. The method used in this study is a qualitative and quantitative methods. Qualitative methods are used to describe supply chain mechanisms and quantitative methods are used to calculate margin values, efficiency levels and farmer’s share. Respondents in this study used the snowball sampling technique. The research data was obtained through interviews, documentation and literature study. The results of this study indicate that there are seven types of rice supply chain flows, namely 1) Farmers – UD Kerta Sari – Consumers, 2) Farmers – Suppliers – UD Kerta Sari – Consumers, 3) Farmers – Suppliers – UD Kerta Sari – Retailers – Consumers, 4 ) Farmers – Suppliers – UD Kerta Sari – Wholesalers – Consumers, 5) Farmers – Suppliers – UD Kerta Sari – Wholesalers – Retailers – Consumers, 6) Farmers – Suppliers – UD Kerta Sari – Collectors – Wholesalers – Consumers, 7) Farmers – Suppliers – UD Kerta Sari – Collectors – Retailers – Consumers. The most efficient type of chainway is the first chainway, because the first type of chainway has the shortest chain. In the first type of chain path, a chain margin of IDR 5,700/kg and a chain efficiency of 6,29%. In the farmer’s share analysis, the first chain path is the most efficient chain path with a farmer’s share value of 49,10%. From the results of the study, it can be concluded that the most efficient supply chain flow from UD Kerta Sari is the first flow. It is suggested to farmers to sell their crops directly to the rice milling place in order to get optimal profits.